Complex character of internal rotation of furfural in the ground S0 and excited S1 electronic states. (November 2020) - Bataev, V.A.; Abramenkov, A.V.; Godunov, I.A.
Highlights: For furfural in the S1 state, the three low-energy vibrational motions are coupled. The reason for one pair of vibrations is the anharmonicity of kinetic energy. The reason for the coupling of other pairs of vibrations is the anharmonicity of potential energy. Accounting for this interaction gives an accurate prediction of frequencies. Abstracts: The forms of potential energy surfaces (PESs), in particular, the potential functions of internal rotation, the heights and forms of potential barriers to internal rotation and the energies of torsional levels, can control some important properties of molecules and substances, as well as the pathways and mechanisms of molecular processes. Usually, the determination of the "experimental" potential function of internal rotation is based on a one-dimensional model due to missing of the experimental data. However, such potential functions are sufficiently accurate only in the cases in which the internal rotation is separated from the other vibrations. Otherwise, the experimental and calculated (quantum chemical) functions can be in serious disagreement. The investigation of PES sections and the comparison of calculated and experimental energies of some vibrational levels proved that internal rotation of furfural in the ground and the first excited singlet electronic states has complex character: two-dimensional (torsion–CHO out-of-plane deformation) and three-dimensional (torsion–CHO out-of-plane deformation–CHald out-of-plane deformation) approximations, respectively.